Demonstration of Simple and Elite Balanced Menu to Increasing Immunity During the Covid-19 Pandemic - Siahaan, Ginta; Nainggolan, Efendi; Lestrina, Dini; Doloksaribu, Bernike; Karimah, Ummu A; Sitorus, Eunike G; Panjaitan, Nuriani; Sinaga, Surya E P (Talenta Publisher Universitas Sumatera Utara, 2023)
A balanced menu is a meal menu consisting of rice, animal side dishes, vegetable side dishes, vegetables and fruits in one meal. This community service aims to provide examples of a balanced menu and maintain a balanced diet as an effort to increase endurance in the midst of the Covid 19 pandemic. This activity is carried out through demonstration methods, giving leaflets, and discussions. The activity participants were the elderly at the Veteran ABRI Housing in Medan Estate Deli Serdang Regency with a total of 20 participants. The balanced menu being demonstrated is a simple and elite balanced nutrition menu, which aims to adjust to the economic conditions of the local community. The results of the activity showed an increase in participants' knowledge about a balanced menu. Before the activity the number of participants who had good knowledge was 16% and after the activity there were 62% of participants who had good knowledge.